I Am Big, It’s the Pictures That Got Small: Sound Technologies and Franz Waxman’s Scores for Sunset Boulevard (1950) and The Twilight Zone’s “The Sixteen Millimeter Shrine” (1959) - Wissner, Reba (Journal of Film Music, 2017)
Franz Waxman composed over 150 film scores, the most famous of which is Billy Wilder’s film noir Sunset Boulevard (1950). The film plot bears a striking resemblance to Rod Serling’s teleplay for The Twilight Zone, “The Sixteen-Millimeter Shrine” (1959). Waxman, composer of the film, was approached to compose a score for a television episode that was what many term a shortened version of Wilder’s film for the small screen, but with supernatural elements. This article serves to remedy the dearth of literature on this topic and to form an examination of the ways that Waxman conceived of music to accompany films with similar themes but on different screens. Through this comparison of the two scores, a clearer picture of Waxman’s approaches to composing music for moving images will be presented.